Protection of Bamboo by Neem Seed Oil - Chandra, Anshul (Indian Forester, 2016)
The present study is an exploration of neem seed oil against bamboo decaying fungi. The neem tree is considered to be a storehouse of various biologically active compounds such as azadirachtin, salanin, nimbin, quercetin etc., all of them are reported to possesses marked anti-microbial and anti-bacterial properties. The neem seed oil exhibited maximum protection of bamboo at its highest concentration and statistically proved to be the best treatment.